the director and the technique of theatrical extemporization (Al-Academy, 2017)
Extemporization is the ability of the actor to reflect his internal being. It gives a sort of confidence and an ability to show the personal countenance of the role away from tension and rigidity. By extemporization, it is possible to deal with and criticize the real living life so it is an intellectual, emotional, sensual, and perceptive process connected with the psychological energy and the emotional memory and all this goes under the control of the director and his instigations and instructions depending on what the text involves of intellectual, social and psychological motivators so it primarily depends on talent, chance and discussion. The research involves four chapters; the first contains the problem which is related to the technique adopted by the director to organize the process of the dramatic extemporization. The importance of the research lies in its focus on one of the acting activities and on identifying the guidance and organization of the extemporization process by the theatrical director. The aim of the research is to identify the director's technique in the extemporization process whereas the limits are restricted to the performances in (2005)the College of Fine Arts. The chapter ends with the definitions of the terminologies. The second chapter which is the theoretical framework involves two parts; the first deals with extemporization as a psychological concept whereas the second deals with the development of this same concept in drama and the chapter finalizes with results of the theoretical framework. The third chapter revolves around the procedures and the samples; two performances have been chosen to study the technique of extemporization. The fourth chapter contains the results the researcher has come up with the most important of which are: 1. Extemporization is considered an essential element with different ratios according to the director and his working technique. 2. The freedom given to the actor varies from one director to the other according to the motivator (the text). 3. Extemporization is shown in the presentation and the acting methods according to the director's view point